Tail Spin - Coulter, Catherine (New York, NY : G.P. Putnam's Sons, 2008)
FBI Special Agents Dillon Savich and Lacey Sherlock are assigned to protect Dr. MacLean, a physician with frontal lobe dementia that could compromise his ability to maintain doctor-patient confidentiality. With a patient list made up of Washington movers and shakers, MacLean's role as a keeper of secrets is jeopardized as well. Is there someone out there so desperate that they'd kill the doctor for what he knows? It is up to Jackson, Savich, and Sherlock to find out--no matter the cost--From publisher description.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Savich, Dillon (Fictitious character) -- Fiction; Sherlock, Lacey (Fictitious character) -- Fiction; Psychiatrists -- Crimes against -- Fiction; Dementia -- Patients -- Fiction; Attempted murder -- Fiction; Legislators -- Family relationships -- Fiction; Large type books; Suspense fiction